Silymarin supplementation could improve the effect of exercise training on high-fat diet-induced metabolic disorders - Behnam Roozbeh; Mohammad Mehdipoor; Gholam Rasul Mohammad Rahimi; Mehrdad Fathei; Tom Clifford; Bibi Pourmirza (Journal of Medicinal Plants)
Background: The use of dietary herbal products as potential anti-obesity agents has gained considerable traction in recent years. Objective: The purpose of the current study was to assess the effects of silymarin supplementation with and without exercise training on a high-fat diet-induced metabolic disorder in male Wistar rats. Methods: 36 male Wistar rats were divided into six groups; 1) control group with a regular diet; 2) high-fat diet (HFD); 3) HFD + Silymarin 25 (S25); 4) HFD + Silymarin 50 (S50); 5) HFD +S25 + ART (aerobic resistance training); 6) HFD + S50+ART (n = 6 for each group). HFD + S25 + ART and HFD + S50 + ART groups performed aerobic exercise three days/week and resistance exercise two days/week. Blood specimens were obtained for biochemical assessments and gene expression at the end of the 12-week intervention. The data were analyzed using one-way ANOVAs and Tukey’s post hoc test with SPSS21 at a significance level of P < 0.05. Results: Final body weight, the levels of glucose, insulin, and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) in all of the treatment groups were significantly less compared with the HFD group (P < 0.05). Lipid profile was significantly improved in treatment groups in comparison with the HFD group (P < 0.05). Leptin and Neuropeptide Y (NPY) levels were significantly lower in HFD + S50, HFD + S25 + ART, and HFD + S50 + ART groups compared to HFD group (P < 0.05). Exercise plus silymarin consumption (HFD + S25 + ART and HFD + S50 + ART) increased Peptide YY levels (PYY) (P= 0.013 and P < 0.001, respectively). Conclusion: Our findings suggest that combined silymarin consumption and exercise training is a promising non-pharmacological treatment for multiple simultaneous HFD-induced risk factors.